“What’s with you people, I’m Blind!”: A content analysis of Avatar: The Last Airbender - Weiser, Abigaile Grace (Kansas State University, 2022)
Introduction: People with disabilities are increasingly represented in television; however, we do not yet know if these representations depict common stereotypes. In this study, I evaluate the popular animated children’s cartoon, Avatar: The Last Airbender, for the presence of disability stereotypes found in previous scholarship. Background: The stereotypes are as follows: the villain, the supercrip, weakness and vulnerability, and the imagery of madness (Safran 1998; Irwin and Moeller 2012; Ellis 2015; Groggin 2009; Schalk 2016). Methods: Episodes were coded according to frequency of characters with disabilities appearances in episodes, how often the portrayal of these characters were stereotypical, and how often they were not. Results: The results suggest characters with disabilities appear often, in more than half of the total episodes. While they are depicted at times in line with stereotypes found in prior literature, they are often portrayed as what I call “neutrally” in scenes or with no stereotype used. Discussion: These results suggest a need to further investigate the presence of the stereotypes in children’s animation and the need to reevaluate their applicability.
Keywords: Children's cartoons; Content analysis; Disability; Stereotypes